Annus Horribilis and its impact on the royal image: How scandals influenced Queen Sofía of Spain’s press coverage in newspapers "El País" and "El Mundo" from 2012 to 2014 - Widlak, Ewa; Pont Sorribes, Carles (Estudios sobre el Mensaje Periodístico, 2015)
The present article analyzes press coverage on the Spanish Queen Sofía of Greece during a time when an outburst of scandals involving different members of the Spanish Royal Family took place. Its main objective is to display changes in the media treatment of the royal spouse caused by these scandals. Research for this article principally involved using content analysis and semiotics to examine coverage on the Queen between 2012 and 2014 in two newspapers, El País and El Mundo. Documentary research and indepth interviews were also used. Paradoxically, findings indicate that when the media most heavily criticized the Crown, the Queen’s image improved.